THE DEVELOPMENT OF THAI COMMUNICATION SKILLS AMONG INTERNATIONAL STUDENTS AT RAJAMANGALA UNIVERSITY OF TECHNOLOGY - Suwannavej , Yutthapoom; Puangsang, Maythika (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2025)
This study aimed to (1) identify effective methods for enhancing the Thai language communication skills of international students at Rajamangala University of Technology (RMUT), (2) develop extracurricular activities to support these skills, and (3) evaluate the effectiveness of the developed activities. A mixed-methods approach was employed with a sample of 42 participants, including instructors and international students. Research instruments included interviews and opinion questionnaires related to the supplementary activities, with a high overall reliability coefficient (α = 0.969). Data were analyzed using frequency, percentage, mean, and standard deviation. The findings revealed the following. First, effective teaching strategies emphasized the development of speaking and listening skills, the use of quality instructional materials, the application of educational psychology principles, contextually appropriate lesson planning, professional teaching commitment, and purposeful integration of technology. Second, five extracurricular activities were developed: Listening with Ears Wide Open (listening), Joyful Chatter (speaking), Focused Vision (reading), Expressive Writing (writing), and Integrated Skill Harmony (skill integration). Third, focus group feedback confirmed the appropriateness of all activities, and post-activity assessments indicated a significant improvement in students’ Thai communication skills, with a statistical significance level of .05. Furthermore, student satisfaction with the activities exceeded the benchmark score of 3.51, also with statistical significance at the .05 level.